Representasi Makna Etika Makan Budaya Jawa dalam Film Kersanan Ndalem - Muhammad Hendi Malik; Gregorius Genep Sukendro (Koneksi, 2021)
"Representation of the Meaning of Javanese Culture Eating Ethics in the Kersanan Ndalem Film" which aims to see the connotation meaning, denotative meaning, and myths of Javanese culture eating ethics contained in the film Kersanan Ndalem. This research uses descriptive qualitative method. The subject of this research is the film Kersanan Ndalem which is a 28-minute documentary film. The data collection technique in this study used observation and documentation and analyzed using Roland Barthes' semiotics model. To test the validity of the data, it was done by collecting and checking some of the data which were deemed appropriate with this study. The results of this research are found various kinds of meanings contained such as: the meaning of politeness, the meaning of respect, the meaning of patience, the meaning of devotion to the meaning of resistance. The meaning of politeness and the meaning of patience can be seen in the tradition of “marak dhahar” carried out in the Yogyakarta Palace which teaches the younger about politeness and patience and respects the elders. The meaning of service can be seen in how the Abdi Dalem sincerely carry out the tasks they have served the Sultan last night. In addition, there is a meaning of struggle which can be seen from how the changes in the function of the banquet that are shown on film. It is hoped that this research can be a lesson for the community in interpreting eating ethics in Javanese culture. “Representasi Makna Etika Makan Budaya Jawa Dalam Film Kersanan Ndalem” bertujuan untuk mengetahui makna konotasi, makna denotasi, dan mitos dari etika makan Budaya Jawa yang terdapat dalam film Kersanan Ndalam. Penelitian ini menggunakan metode kualitatif deskriptif. Subjek dari penelitian ini adalah Film Kersanan Ndalem yang merupakan salah satu film dokumenter berdurasi 28 menit. Teknik pengambilan data pada penelitian ini menggunakan Observasi dan Dokumentasi dan dianalisis menggunakan semiotika model Roland Barthes. Untuk menguji keabsahan data dilakukan dengan cara tiangulasi dilakukan pengecekan dari beberapa data yang dianggap sesuai dengan penelitian ini. Hasil dari penelitian ini adalah ditemukan berbagai macam makna yang terkandung seperti: makna kesopanan, makna penghormatan, makna kesabaran, makna pengabdian hingga makna perjuangan. Makna kesopanan dan makna kesabaran terlihat pada tradisi marak dhahar  yang dilakukan di Keraton Yogyakarta yang mengajarkan kepada yang lebih muda mengenai kesopan dan kesabaran serta mengormati kepada yang lebih tua. Makna pengabdian terlihat pada bagaimana para abdi dalem dengan tulus menjalankan tugas-tugas yang mereka emban semalam mengabdi kepada Sultan. Selain itu, terdapat makna perjuangan yang terlihat dari bagaimana perubahan fungsi dari jamuan makan yang ditampilkan. Diharapkan penelitian ini dapat menjadi pembelajaran bagi masyarakat dalam memaknai etika makan dalam Budaya Jawa.